Temperature-dependent Raman spectroscopy, domain morphology and photoluminescence studies in lead-free BCZT ceramic. Issue 2 (15th January 2021) - Coondoo, Indrani; Panwar, Neeraj; Krylova, Svetlana; Krylov, Alexander; Alikin, Denis; Jakka, Suresh Kumar; Turygin, Anton; Shur, Vladimir Ya.; Kholkin, Andrei L.
Abstract: Present work focuses on detailed temperature-dependent X-ray diffraction, Raman scattering, domain configuration, and photoluminescence (PL) studies in the (Ba0·85 Ca0.15 ) (Zr0·10 Ti0.90 )O3 (BCZT) ceramics. The comprehensive Raman spectroscopy analysis in the present work not only validates the presence of the intermediate orthorhombic phase in BCZT, but also provides evidence of another transition: rhombohedral R 3 c phase to R 3 m at low temperature. Temperature behaviour of the lowest frequency transverse optical mode (soft E (TO) phonon) and hard modes was studied. Temperature dependence of peak positions, intensities, and linewidths of Raman phonon modes signalled the presence of phase transitions near −50 ± 5 °C, 0±5 °C, 35±5 °C and 110 ± 10 °C. Evolution of domain morphology occurring at phase transitions above room temperature was studied by piezoresponse force microscopy technique. Analysis of PL spectra revealed disorder/heterogeneity in the sample and indicated the existence of self-trapped excitons. PL spectra are composed of four distinct colour components ( 2.55eV:blue, 2.32eV:green, 2.08eV:orange and 1.78eV:red).